Posttraumatic Treatment Interventions for Refugee Children Residing in the Middle East and North Africa (MENA) Region: A Brief Review. (2nd January 2022) - Sacca, Lea; Khoury, Stephanie; Maroun, Christelle; Khoury, Milad; Maroun, Veronica; Khoury, Jason; Bouery, Priscilla
ABSTRACT: Despite the tremendous burden of refugees on regional and global health care financial systems, the current tools set into place to deal with the worsening conditions of asylum seekers have failed to address the significant challenges facing the Middle East, which in turn affected the capability of host countries to provide the necessary care for incoming population groups. One of the main health risks refugees in the Middle East and North Africa (MENA) region suffer from is mental health disorders, mainly posttraumatic stress disorder (PTSD), depression, and anxiety. Due to the limited accessibility of mental health services and the shortage of mental health professionals in host communities, refugees end up neglecting their conditions and subsequent consequences, which result in a long-term social, psychological, and economic impact. The following scoping review aims to evaluate PTSD interventions implemented for refugee children in developing nations within the MENA region. The York methodology was used to ensure transparency, enable replication of the search strategy, and increase the reliability of study findings. The results indicate that several strategies such as art therapy, cognitive-behavioral therapy, digital-based educational games, writing for recovery, group theraplay, and profound stress attunement framework deemed effective in decreasing PTSD symptoms on a short-term basis. However, future interventions should apply more sustainable strategies to help refugee children in the long-term management of the chronic mental illness. Additional research regarding this topic is needed in the MENA region.